Effect of dew point temperature and conidium age on germination, germtube growth and infection of maize and sorghum by Peronosclerospora sorghi - Bock, C.H.; Jeger, M.J.; Mughogho, L.K.; Cardwell, K.F.; Mtisi, E. (1999)
The effect of the environment on the germination, survival and infection of sorghum by conidia of Peronosclerospora sorghi is unknown in Africa. Dew point temperature, and the effect of conidium age was characterized for an isolate of P. sorghi from Zimbabwe. Germination and germ tube growth took place in the range 10–34°C (optimal at 10–34 and 20–33°, respectively). Infection was optimal at 14–30°. Incidence of infection at different temperatures was correlated with germ tube growth (r=0·8, P<0·001). Germination and germ tube growth occurred from 5 h after commencing incubation of infected leaf material, although immature conidia harvested at 3 h caused a low incidence of infection. Plant age also affected the incidence of infection. Container grown sorghum plants older than 20 d, and maize plants older than 15 d were resistant to systemic infection by conidia. The results indicate that germination, germ tube growth and infection take place over a wide temperature range, and that some limited biotypic variation may exist when these data are compared to other reports of the environmental requirements of P. sorghi from the U.S.A. and India.